2017
DOI: 10.4142/jvs.2017.18.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Alginate encapsulation preserves the quality and fertilizing ability of Mediterranean Italian water buffalo (Bubalus bubalis) and Holstein Friesian (Bos taurus) spermatozoa after cryopreservation

Abstract: The use of artificial insemination (AI) in buffalo (Bubalus bubalis) is limited by poor ovarian activity during the hot season, seasonal qualitative patterns in semen, low resistance of sperm cells in the female tract, difficulties in estrus detection, and variable estrus duration. Although AI procedures are commonly used in bovine, use of AI has been limited in buffalo. In the zootechnical field, different studies have been conducted to develop techniques for improvement of fertilizing ability of buffalo sper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 36 publications
3
14
1
2
Order By: Relevance
“…Importantly, no significant differences between AIs performed with NRF semen immobilized by the first production line of SV technology (C), which showed the highest levels of sperm DFI (%) and SD DFI in the present study, and conventionally preserved semen was found in a large AI study (Standerholen et al, 2015). It is earlier reported that encapsulated sperm cells are able to fertilize in vivo (Nebel & Saacke, 1994;Nebel et al, 1993;Perteghella et al, 2016;Vishwanath, Nebel, McMillan, Pitt, & Macmillan, 1997).…”
Section: T a B L E 1 Post-thaw Sperm Qualitycontrasting
confidence: 49%
See 3 more Smart Citations
“…Importantly, no significant differences between AIs performed with NRF semen immobilized by the first production line of SV technology (C), which showed the highest levels of sperm DFI (%) and SD DFI in the present study, and conventionally preserved semen was found in a large AI study (Standerholen et al, 2015). It is earlier reported that encapsulated sperm cells are able to fertilize in vivo (Nebel & Saacke, 1994;Nebel et al, 1993;Perteghella et al, 2016;Vishwanath, Nebel, McMillan, Pitt, & Macmillan, 1997).…”
Section: T a B L E 1 Post-thaw Sperm Qualitycontrasting
confidence: 49%
“…It is earlier reported that encapsulated sperm cells are able to fertilize in vivo (Nebel & Saacke, ; Nebel et al., ; Perteghella et al., ; Vishwanath, Nebel, McMillan, Pitt, & Macmillan, ). With the encapsulation technology, the spermatozoa are in a fluid core of an alginate capsule (Nebel et al., ), from which these cells are released at the same time unless an uneven dissolving of the capsules take place.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Furthermore, in an attempt to prolong spermatozoa lifespan in vivo in the female, new semen processing methods have been established. Bovine sperm cells can be encapsulated in alginate beads (Perteghella et al, ) or immobilized by the SpermVital ® technology in solid alginate gel before freezing (Alm‐Kristiansen et al, ; Standerholen et al, ). Common goal for all processing methods is to minimize sperm cryo‐injuries.…”
Section: Introductionmentioning
confidence: 99%